EFFECTIVENESS OF THE SIPENTOLMANIS SERVICE PROGRAM AS A WEBSITE-BASED INTEGRATED SERVICE SYSTEM IN JETIS DISTRICT, MOJOKERTO REGENCY - Anandita, Tasya Ulfa; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The research aims to evaluate how effectively the program functions as a digital public service innovation. Method: A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation using purposive sampling. The analysis was conducted based on four indicators of effectiveness by Budiani (2007), namely target accuracy, program socialization, goal achievement, and program monitoring. Results: Findings reveal that the program has achieved target accuracy as the services align with community needs, although participation remains low due to a preference for face-to-face services. Socialization was limited to the initial launch in 2022, resulting in restricted public awareness. Program goals have been realized through improved efficiency, reduced queues, and more precise services. However, program monitoring has not been optimal due to the absence of formal strategies or policies for evaluation and sustainability. Novelty: This research contributes by applying Budiani’s effectiveness framework comprehensively to assess website-based public service innovation, highlighting the crucial role of continuous socialization and policy support in ensuring the long-term sustainability of digital services at the sub-district level.